Brazil - Municipal Education : Resources, Incentives, and Results, voume 1. Policy Report - World Bank (Washington, DC, 2013)
The study comprises two volumes on the use of public resources to provide educational services in Brazilian municipalities, by which the policy report (volume 1) presents recommendations, based on the research report (volume 2). This research outlines the policy context, objectives, and methodology practiced, to then focus on the extent to which municipalities benefited from efforts designed to provide additional resources for education. A description, and analysis of the patterns of change in the availability of resources, documents the substantial redirection in resources from State governments to Municipal governments that took place during 1996-02, and likewise, from prosperous municipalities, to relatively less prosperous ones, while discussions, and analyses on the composition of expenditures explore issues on the municipal management of such resources, in particular, on specific issues regarding teachers as related to municipal management of resources. The econometric analysis of the educational impact of additional resources, and the management shift of resources from States to Municipalities, shows the educational impact as measured in terms of changes in indicators of internal efficiency of municipal education systems. Policy conclusions suggest efforts should build on the success of previous reforms, by extending the results of successful municipalities to lesser performing ones, with a focus on educational quality, and supported by federal programs that provide financial incentives, and technical assistance.